Using Biowastes to Establish Native Plants and Ecosystems in New Zealand - Simcock, Robyn; Cavanagh, Jo; Robinson, Brett; Gutierrez-Gines, Maria J. (Frontiers in Sustainable Food Systems, 2019)
Biowastes can enhance the establishment of New Zealand (NZ) native vegetation, particularly on degraded land, where biological or physicochemical deficiencies limit plant growth. We identified critical success factors influencing selection and use of biowastes for a) growing native plants and b) rehabilitating native ecosystems. These were: weed competition; resilience (especially to drought and storms); ecosystem succession; and soil microbiome responses to elevated Nitrogen, Phosphorus, Organic Matter (OM) and contaminants (including Trace Elements). These factors determine the selection, timing and methods of biowaste application, selection of plant species and target ecosystems, and post-application management of receiving sites. Commonly planted native NZ species benefit from biowastes application where soils have depleted OM or sites with surface crusting, erosion, or high exposure to wind and temperature fluctuations. Commonly planted native species display luxury uptake of macro-nutrients, even on soils that are low-fertility under agricultural standards. Therefore, the growth responses to additional nutrients may be small. In contrast, most exotic weeds outcompete NZ species in high fertility soils. Therefore, biowaste application should not result in excessive nutrient availability. This can be achieved by using blends that contain a high-carbon biowaste, such as wood-waste, which immobilizes some macronutrients in the short term. We recommend long-term research using mixed-species field trials to identify biowastes and application methods that together support development of resilient native ecosystems. In particular, research should determine the role of biowastes on the beneficial mycorrhizae and native soil fauna. Application methods that enhance heterogeneity may help retain and/or build responsive microbiomes while conserving ‘native’ microbiomes to deliver sustainable, rehabilitated native ecosystems.